A cognitive analysis of Proverbs 1:20–33 - Venter, Pieter M. (HTS teologiese studies, 2019)
This article uses cognitive linguistics and an embodied cognitive approach to analyse the passage of Proverbs 1:20–33. The poem, presented as a prophetic threat, uses metaphoric language to depict the dialogue between personified wisdom and metaphorised human beings. The analysis indicates that there is a coherence of metaphors in the target domain shared by both metaphorised source domains of wisdom and the hearers. Using bodily metaphors it stresses the need of wisdom to be internalised by men.